Dairy manure nutrient recovery reduces greenhouse gas emissions and transportation cost in a modeling study - Feng, Xiaoyu; Smith, Ward; VanderZaag, Andrew C. (Frontiers in Animal Science, 2023)
Manure is a valuable source of nutrients that can be used for crop production. However, liquid manure is typically over 90% water which makes transporting nutrients expensive. Moreover, during storage, liquid manure provides the conditions for methane and other greenhouse gas emissions to occur. Manure processing technology that can separate manure into solid and liquid fractions is interesting for its potential to mitigate emissions and improving the ability to distribute nutrients to land where it is has high value. In this study, the dairy farm model (DairyCrop-Syst) was used to simulate emissions (CH4, N2O, and NH3) and nutrient distribution from a case-study farm in Canada where differing levels of manure processing were implemented, ranging from conventional liquid storage to advanced solid-liquid separation with nutrient recovery. The manure processing system produced a solid fraction with high concentration of N and P, and a liquid fraction containing less nutrients. The solid fraction was simulated to be transported to fields at least 30 km away from the dairy barns, while the liquid fraction was transported by dragline to fields adjacent to the barn. Compared to the baseline system, the addition of solid liquid separation and nutrient recovery reduced methane emissions from the manure storage by 87%, with only a small offset from higher N2O and NH3 emissions from the solid manure fraction. The advanced nutrient separation system resulted in lower transport costs for manure nutrients and the ability to transport N and P to greater distances at less cost.